Potentiating Effect of Clopidogrel and SR 46349, a Novel 5-HT2 Antagonist, on Streptokinase-Induced Thrombolysis in the Rabbit - Herbert, J M; Bernat, A; Sainte-Marie, M; Dol, F; Rinaldi, M (Thrombosis and Haemostasis, 1993)
Current thrombolytic strategies have a number of important shortcomings including resistance to recanalization and development of acute reocclusion. The purpose of this study was to investigate whether the lysis of venous thrombi by streptokinase could be enhanced by SR 46349, a novel 5-HT2 receptor antagonist, or clopidogrel, an analogue of ticlopidine. The activity of these compounds was evaluated by following the lysis of radiolabelled fibrin under a continuous infusion of streptokinase (4,000 IU kg−1 h−1 over 4 h). Streptokinase alone induced 42% thrombolysis when compared to saline. The i. v. co-administration of SR 46349 or clopidogrel (10 mg/kg) enhanced significantly streptokinase-induced thrombolysis. Thrombolysis measured by [125I]-fibrinogen lysis increased to 65 and 59% respectively. This efficacy was achieved without additional prolongation of the template bleeding time observed with streptokinase alone.Thus, the concomitant use of a 5-HT2 receptor antagonist or an anti-ADP agent during streptokinase therapy may facilitate clot lysis.